2009
DOI: 10.3201/eid1506.080684
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Fluoroquinolone-ResistantStreptococcus pneumoniaafter 7-Valent Conjugate Vaccination, Spain

Abstract: Four new genotypes appeared in 2006 after childhood vaccination was begun.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
67
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 39 publications
2
67
1
Order By: Relevance
“…Our results showed that most of the PNS strains (66.2%) were isolated from patients Յ2 years old and PCV7 vaccination led to a considerable coverage in PNS IPD isolates (77.8% for the Յ2-year age group). With the PCV7 NIP, we may now have a considerable decrease in PNS IPD cases in Turkey, as has previously been seen in the United States and in Europe (4,15).…”
mentioning
confidence: 70%
“…Our results showed that most of the PNS strains (66.2%) were isolated from patients Յ2 years old and PCV7 vaccination led to a considerable coverage in PNS IPD isolates (77.8% for the Յ2-year age group). With the PCV7 NIP, we may now have a considerable decrease in PNS IPD cases in Turkey, as has previously been seen in the United States and in Europe (4,15).…”
mentioning
confidence: 70%
“…Prior to the introduction of gatifloxacin and moxifloxacin, all isolates with mutations observed in the QRDRs of S. pneumoniae had mutations in the parC gene (3,10). Since the introduction of gatifloxacin and moxifloxacin, the number of isolates with parC mutations has remained stable, but there has been an increase in the proportion of isolates with gyrA-only mutations (12,13,24).…”
Section: Discussionmentioning
confidence: 99%
“…The oligonucleotide pairs parE398/parE483, parC50/parC152, gyrA44/gyrA170, and gyrB376/ gyrB512 were used to amplify and sequence parE, parC, gyrA, and gyrB QRDRs, respectively (11).…”
Section: Methodsmentioning
confidence: 99%